Exploring tangent-to-curve speed dynamics on two-lane roads in northern Nigeria - Danlami, N. (IAEME Publication, 2017)
The need for safer roads has given rise to exhaustive study of the road geometry and its interaction with other elements. Two-lane rural roads constitute the vast majority of the road network in many developing countries including Nigeria. Similar to inconsistencies in driving speed, it have been established that horizontal curve is also one of those areas were road safety can be improved. This study is aimed at investigating the relationship between speed characteristics of a tangent and the operating speed (V85) at the middle of the horizontal curve succeeding it. The average speed of traffic at the middle of the tangent was considered as the parameter of tangent speed characteristics. Super-elevation, radius and the gradient of the tangent under study were also used as independent variables in the model. Three models were developed with R2-values of 0.532, 0.533 and 0.515 respectively. These R2-values shows that more than 50 of the interaction is explained by the selected variables. It is concluded therefore, the speed characteristics of the preceding tangent can be used to explain the V85 at middle of the succeeding horizontal curve. © IAEME Publication.